A methodology to determine maintenance criticality using Dempster–Shafer theory. (2017) - Bahl, Ankur; Sachdeva, Anish; Garg, Rajiv Kumar
This study deals with the development of a methodology for maintenance policy selection by assimilating the various factors as an alternative to traditional failure mode effect analysis. This methodology is based upon Dempster–Shafer theory (DST) of evidence which helps the plant managers/engineers to contrive an efficacious priority rating of various items of equipment/components under conditions of epistemic uncertainty considering the various parameters. A case study of a distillery plant is undertaken for selection of a suitable maintenance policy for the various items of equipment/components of the plant using the proposed methodology.